Expression of prolyl-hydroxylases PHD-1, 2 and 3 and of the asparagine hydroxylase FIH in non-small cell lung cancer relates to an activated HIF pathway. - Giatromanolaki, A; Koukourakis, M; Pezzella, F; Turley, H; Sivridis, E; Bouros, D; Bougioukas, G; Harris, A; Gatter, K (2008)
The oxygen sensitive prolyl-hydroxylase domain enzymes (PHDs) and the asparagines hydroxylase (FIH, factor inhibiting HIF) regulate the transcriptional activity of HIFs. We assessed the expression of these enzymes in a series of 73 non-small cell lung carcinomas (NSCLC). A direct association of PHDs with FIH and of the PHDs/FIH with HIFs expression was noted. Thirty three of 73 cases had high HIF/PHD expression, predicting intense HIF activity; 19/73 cases had low HIF and high PHD expression mimicking the normal bronchial pattern; and 18/73 cases had low HIF/PHD (inactive HIF pathway). High lactate dehydrogenase LDH5 expression was noted in cases with high HIF/PHD phenotype. The value of such a classification in defining different metabolic phenotypes of NSCLC deserves further evaluation.